Accumulation of 2-oxo acids in mutants of Aspergillus niger requiring lysine - Musílková, M; Panos, J; Sedmera, P; Fencl, Z (Folia microbiologica, 1980)
Mutants of Aspergillus niger 194A and 178 requiring lysine differ from the original prototrophic strain K10 and from each other on the course of accumulation of organic acids. In both mutants less citric acid accumulates during the first phase of cultivation but considerably more 2-oxoglutarate and 2-oxoadipate accumulate than in the original strain. Whereas in the 194A mutant this state remains unchanged also during the second phase of cultivation, in the 178 mutant oxo acids are degraded and citric acid is synthesized intensively. The accumulation of 2-oxoglutarate and 2-oxoadipate in the fermentation medium indicates that in A. niger lysine is synthesized via the homocitrate pathway.
Keywords: Citrates; Aspergillus niger; Lysine; Mutation; ketokyseliny; citráty; lysin; mutace; Keto Acids